2010
DOI: 10.1242/jeb.040030
|View full text |Cite
|
Sign up to set email alerts
|

Oral and integumental uptake of free exogenous glycine by the Japanese spiny lobsterPanulirus japonicusphyllosoma larvae

Abstract: -1). Thus, the results of this study provide clear confirmation that, in addition to the known mode of oral feeding on macroscopic food masses, P. japonicus phyllosoma larvae are also able to absorb nutrients directly from the surrounding medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…they can absorb oxygen and expel dissolved waste products such as CO 2 through their thin, permeable integuments) [40,41]. Some can even absorb nutrients through their body surfaces and metabolize them in their tissues [40,42]. Remarkably, the body-mass scaling slope for metabolism in larvae of the Pacific oyster Crassostrea gigas is not significantly different from that for uptake of the amino acid alanine [40].…”
Section: Discussionmentioning
confidence: 99%
“…they can absorb oxygen and expel dissolved waste products such as CO 2 through their thin, permeable integuments) [40,41]. Some can even absorb nutrients through their body surfaces and metabolize them in their tissues [40,42]. Remarkably, the body-mass scaling slope for metabolism in larvae of the Pacific oyster Crassostrea gigas is not significantly different from that for uptake of the amino acid alanine [40].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, it was believed that the exoskeleton represented an insurmountable barrier to the uptake of dissolved nutrients in arthropod larvae [23,24], and Tonheim et al [22] suggested that methionine was absorbed by Artemia through the gut, with drinking water. However, in a study using isotope-labeled glycine, we have established that the uptake of this AA in Japanese spiny lobster phyllosoma larvae occurs not only via orally ingested water but also, and perhaps primarily, through the integument [21]. This was the first demonstration of integumental absorption of dissolved nutrients in this phylum.…”
Section: Introductionmentioning
confidence: 83%
“…Triplicate water samples were taken from each bowl at 0, 0.5, 1, 2, and 5 h after introduction of the larvae to the bowls. This sampling schedule was based on results from preliminary experiments that showed large individual variability of uptake rates by the larvae in the first hours of incubation and relative stability after 5 h ( [21]; S.C. Söylemez, unpublished results). Samples were taken using 1 ml syringes, passed through a Whatman 0.2 lm PVDF filter, and stored in Eppendorf tubes at -80°C until [27,28] analysis.…”
Section: Amino Acid Analysismentioning
confidence: 99%
See 2 more Smart Citations